IMPLEMENTASI PEMENUHAN PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH DI KABUPATEN MERAUKE - Ruloff Fabian Yohanis Waas; Wilhelmina Jeujanan (SOCIETAS, 2013)
In autonomous era still expand various negative phenomenon among others is the existence of by law forming is which is just ratified and not yet gone into effect effectively have been changed with new perda, less relevant perda with requirement of society. This research to know how far execution in by law forming which have entangled society participation and it is product result with character acomodation in Sub-Province of Merauke. research method the used is research method qualitative by using approach in the form of obtained data directly from responder  interview, documentation and observation, Technique analyse data the used is analytical descriptive, this meant to obtain get good picture, clear and can give data of detail possible about accurate object. Result of this research indicate that implementation accomplishment of society participation in uncommitted by law forming in sub-Province Merauke according to trust of Section sound 96 UU Number 12 Year 2011 and Section 139 sentence ( 1) UU Number 32 Year 2004, and also its clarification can know that, society is entitled to give input in order to preparation or solution of device of by law forming, the society input can be conducted verbally or written and the rights society executed as according to regulation of discipline of area parliament. The mentioned happened because caused many matter one of them because lack of active participation of society in by law making start from process of by law device up to evaluation phase.